2018
DOI: 10.1001/jamaoto.2018.1919
|View full text |Cite
|
Sign up to set email alerts
|

Association of Proton Pump Inhibitors With Hospitalization Risk in Children With Oropharyngeal Dysphagia

Abstract: IMPORTANCE Proton pump inhibitors (PPI) are commonly prescribed to children with oropharyngeal dysphagia and resultant aspiration based on the assumption that these patients are at greater risk for reflux-related lung disease. There is little data to support this approach and the potential risk for increased infections in children treated with PPI may outweigh any potential benefit. OBJECTIVE The aim of this study was to determine if there is an association between hospitalization risk in pediatric patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
(115 reference statements)
0
23
0
Order By: Relevance
“…We are aware, however, of the practice of using PPIs to diagnose GORD by treatment 44. PPIs are designed to suppress acid but have consistently been shown to be ineffective for irritability and fussing in infants with GORD, and they are associated with an increased risk of adverse effects such as infections, allergies and hospital admissions 9 21 35 45 46. There is evidence from Australia to show that PPIs are being over-prescribed for infants with physiological reflux and symptoms of colic who may or do not have GORD.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware, however, of the practice of using PPIs to diagnose GORD by treatment 44. PPIs are designed to suppress acid but have consistently been shown to be ineffective for irritability and fussing in infants with GORD, and they are associated with an increased risk of adverse effects such as infections, allergies and hospital admissions 9 21 35 45 46. There is evidence from Australia to show that PPIs are being over-prescribed for infants with physiological reflux and symptoms of colic who may or do not have GORD.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study in paediatrics showed a nearly twofold increase in hospitalisations for children with dysphagia who were treated with a PPI compared with untreated children. 47 A large population-based cohort study demonstrated a twofold increased risk of community-acquired pneumonia in children treated with PPIs compared with controls with an even greater risk in children with disability. 5 Further, children with NI have increased baseline risk of low bone mineral density and fractures as well as alterations in gut flora if they are enterally fed.…”
Section: Discussionmentioning
confidence: 99%
“…An explanation for this could be that the decision to prescribe AST for specific patients was left to individual providers. There is also variation even within each provider's cohort over time as data have emerged showing potential for significant complications with use of AST 18, 19 . These cohorts of patients should be further investigated to determine whether PAS score may be a useful predictor of which patients will benefit from AST and which will not.…”
Section: Discussionmentioning
confidence: 99%